Dynamics of IFN-β Responses during Respiratory Viral Infection. Insights for Therapeutic Strategies - Watson, Alastair; Spalluto, C. Mirella; McCrae, Christopher; Cellura, Doriana; Burke, Hannah; Cunoosamy, Danen; Freeman, Anna; Hicks, Alex; Hühn, Michael; Ostridge, Kristoffer; Staples, Karl J.; Vaarala, Outi; et al. (American journal of respiratory and critical care medicine, 2020)
Viral infections are major drivers of exacerbations and clinical burden in patients with asthma and chronic obstructive pulmonary disease (COPD). IFN-β is a key component of the innate immune response to viral infection. To date, studies of inhaled IFN-β treatment have not demonstrated a significant effect on asthma exacerbations. The dynamics of exogenous IFN-β activity were investigated to inform on future clinical indications for this potential antiviral therapy. Monocyte-derived macrophages (MDMs), alveolar macrophages, and primary bronchial epithelial cells (PBECs) were isolated from healthy control subjects and patients with COPD and infected with influenza virus either prior to or after IFN-β stimulation. Infection levels were measured by the percentage of nucleoprotein 1-positive cells using flow cytometry. Viral RNA shedding and IFN-stimulated gene expression were measured by quantitative PCR. Production of inflammatory cytokines was measured using MSD. Adding IFN-β to MDMs, alveolar macrophages, and PBECs prior to, but not after, infection reduced the percentage of nucleoprotein 1-positive cells by 85, 56, and 66%, respectively ( < 0.05). Inhibition of infection lasted for 24 hours after removal of IFN-β and was maintained albeit reduced up to 1 week in MDMs and 72 hours in PBECs; this was similar between healthy control subjects and patients with COPD. IFN-β did not induce inflammatory cytokine production by MDMs or PBECs but reduced influenza-induced IL-1β production by PBECs. modeling of IFN-β dynamics highlights the potential for intermittent prophylactic doses of exogenous IFN-β to modulate viral infection. This provides important insights to aid the future design of clinical trials of IFN-β in asthma and COPD.